Transparent Magnesium Aluminate Spinel Ceramics Reinforced by Alumina Nanofibers; Russian Physics Journal; Vol. 67, iss. 9 - Paygin V. D. Vladimir Denisovich; Shevchenko I. N. Ivan Nikolaevich; Deulina D. E. Darjya Evgenjevna; Dvilis E. S. Edgar Sergeevich; Khasanov O. L. Oleg Leonidovich; Stepanov S. A. Sergey Aleksandrovich; Valiev D. T. Damir Talgatovich (2024, 2024)
Title screen